Managing and using MySQL. - Reese, George, 1969-; King, Tim, ....-; Yarger, Randy Jay, ....- (Beijing : O'Reilly, 2002)
Samenvatting:Learn how to use MySQL, a popular database product that supports keysubsets of SQL on Linux and Unix systems. Using C/C++, Java, Perl, PHP,or Python, you can write programs to interact with a MySQL database,either as a stand-alone application or through a web page. This bookcovers the whole process, from installation to programming interfaces anddatabase administration. It includes ample tutorial material and examples
Keywords: Gegevensbanken; Programmeertalen; Query-talen.; Www world wide web